THE EFFECT OF PWIM (PICTURE WORD INDUCTIVE MODEL) ON STUDENTS’ COMPETENCE IN WRITING NARRATIVE TEXT - Sabrina, Kisti; Kamaluddin, Kamaluddin; Sapan, Yulius Tandi (Journal of Teaching of English, 2020)
This research aimed at investigating whether there is a significant effect of Picture Word Inductive Model on students’ competence in writing narrative text. The design of this research was Pre-Experimental design one group pre test and post test. The population of this research was all first grade of class IPA of Senior High School 4 Wangi-Wangi. The sample of this research was class IPA 1 which consists of 20 students. The instrument of this research was writing test in narrative genre and the criteria of students’ writing were assessed from five aspects of writing, namely content, organization, language use, vocabulary and mechanics. The data were obtained by using two essay writing tests. They were pre-test and post-test. The pre-test was given before treatment and the post-test was given after treatments in order to know the students’ competence before and after treatment of Picture Word Inductive Model.  The data were analyzed by using SPSS in form of Paired Sample T-test. The result of the analysis showed that there was a significant effect of Picture Word Inductive Model on students’ competence in writing narrative text. It proved by the result of hypothesis testing using paired sample t-test. The mean score of pre-test was 59.77 and mean score of post-test was 76.67. Moreover, as a result the probability score of .000 (p score) was less than the level of significance (p ≤ 0.50. Therefore, it can be said that using Picture Word Inductive Model gives significant effect to increase students’ competence in writing narrative text at class IPA 1 of Senior High School 4 Wangi-Wangi.